The Ecological Vision of Space in Gary Snyder’s Ecopoetry - Dahal, Arvind (Interdisciplinary Journal of Management and Social Sciences, 2021)
The paper seeks to investigate the ecological vision of Space in Gary Snyder’s ecopoetry which exclusively exposes how humans have modified the planetary space naively and accelerated it greatly in the name of promoting technology and consumption oriented industrial economy. Snyder’s ecopoetry is a poetic response to the growing environmental concerns and he aims to reconnect humans to nature in the face of a threatened world. Snyder’s poems; “The Berry Feast”, “Mid-August at Sourdough Mountain Lookout”, “By Frazier Greek” and “Riprap” are analyzed in the light of his “Deep Ecological” movement and the central environmental problem of Space which reminds us that our planetary space is limited, and the growing threats to that space require us to reconsider our relationship to that space and use of it. My contention in this paper is to argue that Snyder views the boundary made between humans and nonhumans, place and non-place as hubristic in nature because humans are still insouciant about where the boundaries originated. Theoretical insights from Henri Lefebvre, Lawrence Buell, Martin Heidegger, HomiBhaba, Marc Auge, Yi-Fu Tuan and Gary Snyder reframe the relationships of humans to the natural world, in this paper. Their conceptions of those relationships are premised on a particular idea of space as boundaried: this is the human world and that is the natural one.